From Political Clientelism to Participatory Democracy - Abdur Rozaki (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2022)
The Act of Village has given many opportunities for villages in Indonesia to generate innovation in the local contexts. The governance for village development creates a new way to develop the rural area through visionary leadership innovation. This study showcases two villages that can encourage modernism in innovative leadership, namely Panggungharjo Village and Sayan Village. These villages have been able to promote local democratization from political clientelism to good governance. This study presented social change by the Most Significant Change (MOS) approach that involves two headmen in the site of engagement community. The critical finding of this study is directed into three notions. First, a contestation of village election is free from clientelistic and money politics. Second, the program is oriented toward citizenship. Third, the governing authority in the local village is given by the resources in the form of village funds allocated in a targeted and legal manner to support community empowerment. In this community service, community organizing to realize good governance practices through innovative leadership is a central issue in the sustainable development of the village